Two-agent type liquid crystal panel copper acid etching solution and preparation method and application thereof
By adding specific components to the two-dosage liquid crystal panel copper acid etching solution, the problems of short service life and weakened etching capacity of the existing etching solution are solved, and a longer service life and more stable etching performance are achieved.
Patent Information
- Application Number
- CN202411728147.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The use period of the existing two-dose etching liquid during the etching process is shorter, and the etching capacity is weakened after 48 hours, making it easy to have problems such as two-stage angles and Mo tailings.
A two-dose liquid crystal panel copper acid etching liquid is designed, and the copper ion load capacity and service life are improved by adding specific components, such as hydrogen peroxide, acidic substances, organic alkalis, corrosion inhibitors, chelating agents and stabilizers to the main and auxiliary agents of the etching liquid, are added.
The use cycle of the main agent during the etching process has been extended, and the etching capacity has not weakened after 48 hours. In addition, no problems such as two-section angles and Mo tailings have occurred under high copper ion content, which has significantly improved the use value of the etching liquid.
Smart Images

Figure CN119530808A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of etching solutions, and in particular relates to a two-dose type liquid crystal panel copper acid etching solution and a preparation method and application thereof. Background Art
[0002] High-resolution, low-power TFT-LCD displays have become the main direction of technology research and development for LCD panel manufacturers. Copper has a much lower resistivity than aluminum, which can reduce wiring resistance, improve charging rate and pixel opening rate, and solve the resistance / capacitance time delay problem caused by the high resistance of traditional aluminum interconnection process on large-size TV products, which is favored by panel companies in the industry.
[0003] The metal film formed by the copper metal material itself has poor adhesion to the glass substrate whose main component is silicon dioxide. In addition, copper itself will diffuse with silicon to form copper silicide under the high temperature of non-metallic layer film formation. At the same time, the copper surface is easily oxidized in the air to form cuprous oxide. Both of these points will produce very high contact resistance, so a suitable substrate must be selected to increase adhesion and prevent copper metal diffusion.
[0004] For copper wire technology, the etching solutions of two-layer metal structures such as Cu / Mo, Cu / Ti, Cu / MTD, and Cu / MoNb have been used in mass production in the industry. However, the top metal copper of the two-layer structure has the risk of oxidation, and the top metal copper also has the risk of diffusion to the upper gate insulation layer, increasing the resistance of the wire; therefore, the above risks are currently avoided by using a three-layer metal structure, including MTD-Cu-MTD, MoNb-Cu-MoNb, MoNb-Cu-MTD and other structures.
[0005] During the etching process of the three-layer metal etching solution, due to the influence of the electrochemical effect, the etching rate of the top alloy layer is too slow, and the top metal protrudes, that is, the "roof" phenomenon. Or the etching rate of the top alloy layer is too fast, resulting in serious side etching of the top metal, which may cause photoresist peeling, that is, over-etching problem. At the same time, the bottom alloy layer may have a two-stage angle problem due to the electrochemical effect. Therefore, in order to solve the above problems, the present application provides a two-dose liquid crystal panel copper acid etching solution. Summary of the invention
[0006] The technical problem solved by the present invention is that the two-agent etching solution prolongs the service life of the main agent in the etching process, and after 48 hours, the etching ability is weakened, and the second-stage corner and Mo tailing appear.
[0007] In view of the technical problems existing in the prior art, the present invention designs a two-component copper acid etching solution for liquid crystal panels and a preparation method and use thereof. The two-component copper acid etching solution of the present invention has a high copper ion loading capacity and a long service life. The two-component etching solution can extend the service life of the main agent in the etching process, and the etching ability remains unchanged after 48 hours. Moreover, as the copper ion content increases to 14000ppm, no second-stage angle, Mo tailing and the like occur during the entire etching reaction process, and the etching solution has excellent use value.
[0008] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising" and similar meanings, and closed-ended "consisting of..." and similar meanings.
[0009] In order to solve the above-mentioned technical problems, the present invention adopts the following solutions:
[0010] A two-component liquid crystal panel copper acid etching solution, comprising an etching solution main agent and an etching solution auxiliary agent, characterized in that, calculated by weight, the etching solution main agent comprises the following components:
[0011] 5-20 parts of hydrogen peroxide;
[0012] 5-15 parts of acidic substances;
[0013] 3-10 parts of organic base;
[0014] Corrosion inhibitor 0.01-0.1 part;
[0015] Chelating agent 0.01-0.08 part;
[0016] Stabilizer 0.3-2 parts;
[0017] 60-80 parts of deionized water;
[0018] The etching solution auxiliary agent includes the following components:
[0019] 30-45 parts of acidic substances;
[0020] 30-50 parts of organic base;
[0021] Corrosion inhibitor 0.02-0.2 parts;
[0022] Stabilizer 0.3-2 parts;
[0023] 40-60 parts of deionized water.
[0024] Furthermore, the acidic substance is one or more of formic acid, propionic acid, phthalic acid, citric acid, oxalic acid, malic acid, malonic acid, glycolic acid, succinic acid, tartaric acid, acetic acid, and hydroxybenzenesulfonic acid;
[0025] The organic base is one or more of isopropanolamine, isobutanolamine, triethanolamine, dimethylethanolamine, diethylaminopropylamine, diethylenetriamine, tetramethylammonium hydroxide and tetrapropylammonium hydroxide.
[0026] Furthermore, the corrosion inhibitor is one or more of 3-amino-1,2,4-triazole, 5-aminotetrazolyl, benzotriazole, 6-nitrobenzimidazole, 2-aminothiazole, and 3-amino-1,2,4-triazole.
[0027] Furthermore, the corrosion inhibitors are 3-amino-1,2,4-triazole and benzotriazole.
[0028] Furthermore, the mass ratio of the 3-amino-1,2,4-triazole to benzotriazole is 2-10:3-8.
[0029] Furthermore, the chelating agent is one or more of N-acetylneuraminic acid pentamer α(2-8), N-acetylneuraminic acid methyl ester, N, acetylneuraminic acid 2,4,7,8,9-pentaacetate, N-acetyl-2,3-didehydro-2-deoxyneuraminic acid, and N-acetylneuraminic acid dimer α(2-8).
[0030] Furthermore, the stabilizer is p-hydroxybenzenesulfonic acid and / or N-phenylurea.
[0031] The present invention also discloses a method for preparing the above-mentioned two-component liquid crystal panel copper acid etching solution, which is characterized by comprising the following steps:
[0032] Step 1: Weigh the respective components of the etching solution main agent and the etching solution auxiliary agent;
[0033] Step 2: Mix and stir the components evenly to obtain a two-component liquid crystal panel copper acid etching solution.
[0034] The invention also discloses a use of the two-dose liquid crystal panel copper acid etching solution for etching a MoNb-Cu-MoNb liquid crystal panel.
[0035] The present invention also discloses an etching method of the above two-component liquid crystal panel copper acid etching solution, which is characterized by comprising the following steps:
[0036] Step 1: Immerse the MoNb-Cu-MoNb glass substrate in the above etching solution and start timing;
[0037] Step 2: placing the etched glass substrate in ultrapure water and rinsing for 30 seconds;
[0038] Step 3: Blow dry the rinsed glass substrate with nitrogen.
[0039] In the present invention, in order to further optimize the effect of the etching solution, each component can be optimized, the etching solution main agent: 10-16 parts of hydrogen peroxide; 6-13 parts of acidic substances; 5-8 parts of organic bases; 0.02-0.09 parts of corrosion inhibitors; 0.02-0.06 parts of chelating agents; 0.5-1.8 parts of stabilizers; 65-75 parts of deionized water; etching solution auxiliary agents: 33-40 parts of acidic substances; 35-45 parts of organic bases; 0.04-0.18 parts of corrosion inhibitors; 0.5-1.8 parts of stabilizers; 45-55 parts of deionized water.
[0040] In the present invention, the acidic substance is preferably malonic acid.
[0041] In the present invention, the organic base is preferably dimethylethanolamine and / or triethanolamine.
[0042] In the present invention, the mass ratio of 3-amino-1,2,4-triazole to benzotriazole is preferably 3:2.
[0043] In the present invention, the corrosion inhibitor is selected to be used in combination with 3-amino-1,2,4-triazole and benzotriazole, so that as the copper ion content increases during the etching reaction, the etching rate remains stable and no transition change occurs. The possible reason is that the two corrosion inhibitors are adsorbed at the interface between the metal copper and the etching solution during the etching reaction, thereby achieving the effect of regulating the etching rate.
[0044] In the present invention, the chelating agent is preferably N-acetylneuraminic acid pentamer α(2-8).
[0045] In the present invention, the chelating agent N-acetylneuraminic acid pentamer α (2-8) contains a variety of active groups, which can be adsorbed on the interface between metal and etching solution and the metal surface to control the etching rate; it can also be complexed with metal ions to reduce the generation of free radicals, reduce the decomposition rate of hydrogen peroxide, maintain the pH of the etching solution, and make the acidic environment almost unchanged within 48 hours of etching reaction, further ensuring the safety and stability of the etching reaction, and playing the dual role of corrosion inhibition and chelation; and it has stronger water solubility and better stability than N-acetylneuraminic acid.
[0046] In the present invention, the two-component liquid crystal panel etching solution can also be used to etch Cu-MoNb liquid crystal panels.
[0047] In the present invention, the etching method of the two-component liquid crystal panel etching solution includes using the etching solution main agent to etch copper metal, and as the copper ion content increases, adding the etching solution auxiliary agent with 8-15 times the copper concentration to the etching solution main agent.
[0048] The present invention provides a two-component liquid crystal panel copper acid etching solution and a preparation method and use thereof, which have the following beneficial effects:
[0049] 1. In the two-component copper acid etching solution for liquid crystal panels of the present invention, the chelating agent has the dual functions of corrosion inhibition and chelation, and can also adjust the pH value of the main agent, stabilize the etching environment of the etching solution, and extend the service life of the main agent during the etching process. The etching ability of the two-component etching solution remains consistent after 48 hours, and the pH and hydrogen peroxide content remain stable.
[0050] 2. The two-component copper acid etching solution for liquid crystal panels of the present invention does not contain substances such as fluorine and phosphorus, which greatly reduces the cost of waste liquid treatment and protects the environment.
[0051] Therefore, the two-component liquid crystal panel copper acid etching solution of the present invention is used in the display panel MoNb-Cu-MoNb (Cu layer thickness is The thickness of MoNb is ) The etching field has very good application prospects and potential for large-scale industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 : This is the SEM image after MoNb-Cu-MoNb etching at 0h 500ppm using Example 1, with a magnification of 40,000 times.
[0053] Figure 2 : This is the SEM image after MoNb-Cu-MoNb etching at 14000ppm at 0h using Example 1, with a magnification of 40000 times.
[0054] Figure 3 : This is the SEM image after MoNb-Cu-MoNb etching at 500ppm for 24h using Example 1, with a magnification of 40,000 times.
[0055] Figure 4 : This is the SEM image after MoNb-Cu-MoNb etching at 14000ppm for 24h using Example 1, with a magnification of 40000 times.
[0056] Figure 5 : This is the SEM image after MoNb-Cu-MoNb etching at 500ppm for 48h using Example 1, with a magnification of 40,000 times.
[0057] Figure 6: This is the SEM image after MoNb-Cu-MoNb etching at 14000ppm for 48h using Example 1, with a magnification of 40000 times.
[0058] Figure 7 : This is the SEM image of MoNb-Cu-MoNb after etching at 14000ppm at 0h using Comparative Example 1, with a magnification of 10000 times. DETAILED DESCRIPTION
[0059] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings:
[0060] Examples 1-6 and Comparative Examples 1-3 disclose a variety of two-component copper acid etching solutions for liquid crystal panels, including an etching solution main agent and an etching solution auxiliary agent as shown in Table 1, and specific components contained in the etching solution main agent and the etching solution auxiliary agent are shown in Table 2 and Table 3.
[0061] Table 1 Examples 1-6, Comparative Examples 1-3
[0062] Main agent Adjuvants Example 1 Etching liquid main agent 1 Etching liquid auxiliary agent 1 Example 2 Etching liquid main agent 2 Etching liquid auxiliary agent 2 Example 3 Etching liquid main agent 3 Etching liquid auxiliary agent 3 Example 4 Etching liquid main agent 4 Etching liquid auxiliary agent 4 Example 5 Etching liquid main agent 5 Etching liquid auxiliary agent 5 Example 6 Etching liquid main agent 6 Etching liquid auxiliary agent 6 Comparative Example 1 Comparison of main agent 1 Comparative adjuvant 1 Comparative Example 2 Compare main agent 2 Comparative adjuvant 1 Comparative Example 3 Comparison of main agent 3 Comparative adjuvant 1
[0063] Table 2 Etching solution main agent 1-6, comparative main agent 1-3
[0064]
[0065]
[0066] Table 3 Etching liquid auxiliary agents 1-6, comparative auxiliary agent 1
[0067]
[0068] Table 4 Test data
[0069]
[0070]
[0071] It can be seen from the data in Table 4 that the etching rate stability of Examples 1-6 is better, the etching rate decay rate, 48h pH increase, and 48h H2O2 decay rate are all lower, and there is no metal residue (MoNb residue).
[0072] About the preparation method of the etching solution of the present invention:
[0073] The present invention relates to the preparation of multiple groups of etching solutions, and the preparation methods thereof are all prepared by referring to the following method:
[0074] Step 1: Weigh the respective components of the etching solution main agent and the etching solution auxiliary agent;
[0075] Step 2: Mix and stir the components evenly to obtain a two-component liquid crystal panel copper acid etching solution.
[0076] About etching method:
[0077] Step 1: Immerse the MoNb-Cu-MoNb glass substrate in the above etching solution and start timing;
[0078] Step 2: placing the etched glass substrate in ultrapure water and rinsing for 30 seconds;
[0079] Step 3: Blow dry the rinsed glass substrate with nitrogen.
[0080] About performance testing and description:
[0081] Performance 1 Etching rate stability test method is:
[0082] The etching solution was subjected to a time experiment of 0h, 24h, and 48h, and the etching rate, pH value, and hydrogen peroxide content at each time were recorded.
[0083] Performance 2 Metal Residue (MoNb Residue), Second Angle, Mo Tailing Test Method is:
[0084] The MoNb-Cu-MoNb glass substrate ( ) was placed in the etching solution for etching time of 115 s, and the etched glass substrate was subjected to SEM inspection to observe whether there was metal residue on the surface after etching, Mo tailing and two-stage corner phenomenon.
[0085] Analysis of the test results:
[0086] The two-dose etching solution of the embodiment of the present invention has a stable etching ability after 48 hours, and the overall pH value of the etching solution remains unchanged, and the hydrogen peroxide content decays very little.
[0087] In Comparative Example 1, since the etching solution lacks the addition of the chelating agent N-acetylneuraminic acid pentamer α(2-8), as the copper ion content increases, the divalent copper ions cannot be chelated, so the hydrogen peroxide content decreases sharply, affecting the etching ability.
[0088] In Comparative Example 2, since the chelating agent in the etching solution is ethylenediaminetetraacetic acid, its ability to chelate metal ions is not strong. Later, as the copper ion content increases, the metal chelate will form crystals and precipitate, resulting in poor subsequent etching of the substrate.
[0089] In Comparative Example 3, due to the lack of the stabilizer p-hydroxybenzenesulfonic acid in the etching solution, the amount of HO.2 continued to increase, hydrogen peroxide was unstable, and the etching effect became worse.
[0090] Further comparison is made through the attached drawings in the specification:
[0091] Figure 1 This is a SEM image of MoNb-Cu-MoNb after etching at 0h 500ppm using Example 1, with a magnification of 40,000 times. Figure 1 It can be seen that there is no second angle after etching and no Mo tailing is produced, indicating that the etching effect is good.
[0092] Figure 2 This is a SEM image of MoNb-Cu-MoNb after etching at 14000ppm at 0h using Example 1, with a magnification of 40000 times. Figure 2 It can be seen that the etching performance is intact without degradation.
[0093] Figure 3 This is a SEM image of MoNb-Cu-MoNb after etching at 500ppm for 24h using Example 1, with a magnification of 40,000 times. Figure 3 It can be seen that the etching performance is intact without degradation.
[0094] Figure 4 This is a SEM image of MoNb-Cu-MoNb after etching at 14000ppm for 24h using Example 1, with a magnification of 40000 times. Figure 4 It can be seen that the etching performance is intact without degradation.
[0095] Figure 5 This is a SEM image of MoNb-Cu-MoNb after etching at 500ppm for 48h using Example 1, with a magnification of 40,000 times. Figure 5 It can be seen that the etching performance is intact without degradation.
[0096] Figure 6 This is a SEM image of MoNb-Cu-MoNb after etching at 14000ppm for 48h using Example 1, with a magnification of 40000 times. Figure 6 It can be seen that the etching performance is intact without degradation.
[0097] Figure 7 This is a SEM image of MoNb-Cu-MoNb after etching at 14000ppm at 0h using Comparative Example 1, with a magnification of 10000 times. Figure 7 It can be seen that there is obvious metal residue and the etching ability is significantly weakened.
[0098] The chelating agent in the two-component copper acid etching solution of the present invention has the dual functions of corrosion inhibition and chelation, and can also adjust the pH value of the main agent, stabilize the etching environment of the etching solution, and extend the service life of the main agent in the etching process. The etching ability of the two-component etching solution remains consistent after 48 hours, and the pH and hydrogen peroxide content remain stable.
[0099] The present invention is described exemplarily above in conjunction with the embodiments and drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned methods. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A two-component copper acid etching solution for liquid crystal panels, comprising an etching solution main agent and an etching solution auxiliary agent, characterized in that: The etching solution main agent includes the following components in parts by weight: The etching solution auxiliary agent includes the following components:
2. A two-component liquid crystal panel copper acid etching solution according to claim 1, characterized in that: The acidic substance is one or more of formic acid, propionic acid, phthalic acid, citric acid, oxalic acid, malic acid, malonic acid, glycolic acid, succinic acid, tartaric acid, acetic acid, and hydroxybenzenesulfonic acid; The organic base is one or more of isopropanolamine, isobutanolamine, triethanolamine, dimethylethanolamine, diethylaminopropylamine, diethylenetriamine, tetramethylammonium hydroxide and tetrapropylammonium hydroxide.
3. A two-component copper acid etching solution for liquid crystal panels according to claim 1, characterized in that: The corrosion inhibitor is one or more of 3-amino-1,2,4-triazole, 5-aminotetrazolyl, benzotriazole, 6-nitrobenzimidazole and 2-aminothiazole.
4. A two-component copper acid etching solution for liquid crystal panels according to claim 3, characterized in that: The corrosion inhibitors are 3-amino-1,2,4-triazole and benzotriazole.
5. A two-component copper acid etching solution for liquid crystal panels according to claim 1, characterized in that: The chelating agent is one or more of N-acetylneuraminic acid pentamer α(2-8), N-acetylneuraminic acid methyl ester, N, acetylneuraminic acid 2,4,7,8,9-pentaacetate, N-acetyl-2,3-didehydro-2-deoxyneuraminic acid, and N-acetylneuraminic acid dimer α(2-8).
6. A two-component copper acid etching solution for liquid crystal panels according to claim 1, characterized in that: The stabilizer is p-hydroxybenzenesulfonic acid and / or N-phenylurea.
7. A method for preparing a two-component liquid crystal panel copper acid etching solution according to any one of claims 1 to 6, characterized in that The following steps are involved: Step 1: Weigh the respective components of the etching solution main agent and the etching solution auxiliary agent; Step 2: Mix and stir the components evenly to obtain a two-component liquid crystal panel copper acid etching solution.
8. An etching method for a two-component liquid crystal panel copper acid etching solution according to any one of claims 1 to 6, characterized in that The following steps are involved: Step 1: Immerse the MoNb-Cu-MoNb glass substrate in the above etching solution and start timing; Step 2: placing the etched glass substrate in ultrapure water and rinsing for 30 seconds; Step 3: Blow dry the rinsed glass substrate with nitrogen.
9. Use of the two-component copper acid etching solution for liquid crystal panels according to any one of claims 1 to 6 for etching MoNb-Cu-MoNb liquid crystal panels.
Citation Information
Cited By
Cu-MTD alloy etching solution composition and application thereof
CN121161292A
Two-agent type copper etching solution and preparation method thereof
CN122105406A